What's the relationship between the two numbers?

Algebra Level 2

18 + 3 18 + 3 18 + 3 18 + = ? \large \sqrt{18 + 3 \sqrt{ 18 + 3 \sqrt {18 + 3 \sqrt{ 18 + \ldots}}}} = \ ?


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

Sravanth C.
May 3, 2015

According to the question, 18 + 3 18 + 3 18 + 3 18 + = x \large \sqrt{18 + 3 \sqrt{ 18 + 3 \sqrt {18 + 3 \sqrt{ 18 + \ldots}}}} = \ x

Or, 18 + 3 x = x \large \sqrt{18 + 3x} = \ x

Squaring both the sides , 18 + 3 x = x 2 \large 18+3x= x^{2}

Or, x 2 3 x 18 = 0 \large x^{2}-3x-18=0

Or, x 2 6 x + 3 x 18 = 0 \large x^{2}-6x+3x-18=0

Or, x ( x 6 ) + 3 ( x 6 ) \large x(x-6)+3(x-6)

Or, ( x 6 ) ( x + 3 ) \large (x-6)(x+3)

Therefore, we get x = 6 \large x=6 or, x = 3 \large x=-3

As the answer can't be negative we can ignore the second value of x x .

Therefore, x = 6 x=6 , i.e. 18 + 3 18 + 3 18 + 3 18 + = 6 \large \sqrt{18 + 3 \sqrt{ 18 + 3 \sqrt {18 + 3 \sqrt{ 18 + \ldots}}}} = \ 6

This doesn't explain why x x has to exist. It's possible that the expression diverges.

Ivan Koswara - 6 years, 1 month ago

Log in to reply

He probably does not understand what you are saying. Don't worry he will take time :P

Nitesh Chaudhary - 5 years, 9 months ago

Why under root 18+3x =x?

Mehdia Nadeem - 6 years ago

Log in to reply

Because the pattern is being repeated infinitely.

Sravanth C. - 6 years ago
Ivan Koswara
May 4, 2015

This is just another variant of the classic x + x + \sqrt{x + \sqrt{x + \ldots}} problem.

Observe that the expression is the limit of the sequence { a n } \{a_n\} where a 1 = 18 , a n + 1 = 18 + 3 a n a_1 = \sqrt{18}, a_{n+1} = \sqrt{18 + 3a_n} for all n 1 n \ge 1 . We claim that:

  • a n < a n + 1 a_n < a_{n+1}
  • 0 < a n < 6 0 < a_n < 6

by induction on n n .

As the base case, 0 < a 1 < 6 0 < a_1 < 6 is clear. It can also be computed that a 2 > a 1 a_2 > a_1 : since 18 + 3 18 > 18 18 + 3\sqrt{18} > 18 and the function x x x \mapsto \sqrt{x} is increasing, 18 + 3 18 > 18 \sqrt{18 + 3\sqrt{18}} > \sqrt{18} as well, showing that a 2 > a 1 a_2 > a_1 .

Suppose we have proven the claim for n = n 0 1 n = n_0 - 1 , where n 0 2 n_0 \ge 2 . We'd like to prove the claim for n = n 0 n = n_0 .

We have,

a n 0 = 18 + 3 a n 0 1 > 18 + 3 0 = 18 > 0 \begin{aligned} a_{n_0} &= \sqrt{18 + 3 a_{n_0 - 1}} \\ &> \sqrt{18 + 3 \cdot 0} \\ &= \sqrt{18} > 0 \end{aligned}

Also,

a n 0 = 18 + 3 a n 0 1 < 18 + 3 6 = 36 = 6 \begin{aligned} a_{n_0} &= \sqrt{18 + 3 a_{n_0 -1}} \\ &< \sqrt{18 + 3 \cdot 6} \\ &= \sqrt{36} = 6 \end{aligned}

Finally,

a n 0 2 a n 0 1 2 = ( 18 + 3 a n 0 1 ) a n 0 1 2 = ( a n 0 1 + 3 ) ( a n 0 1 6 ) \begin{aligned} a_{n_0}^2 - a_{n_0-1}^2 &= (18 + 3 a_{n_0 - 1}) - a_{n_0 - 1}^2 \\ &= -(a_{n_0-1} + 3)(a_{n_0-1} - 6) \end{aligned}

Since 0 < a n 0 1 < 6 0 < a_{n_0-1} < 6 by inductive hypothesis, we have a n 0 1 + 3 > 0 a_{n_0-1}+3 > 0 and a n 0 1 6 < 0 a_{n_0-1} - 6 < 0 , giving ( a n 0 1 + 3 ) ( a n 0 1 6 ) > 0 -(a_{n_0-1} + 3)(a_{n_0-1} - 6) > 0 . But ( a n 0 1 + 3 ) ( a n 0 1 6 ) = a n 0 2 a n 0 1 2 -(a_{n_0-1} + 3)(a_{n_0-1} - 6) = a_{n_0}^2 - a_{n_0-1}^2 , so a n 0 2 a n 0 1 2 > 0 a_{n_0}^2 - a_{n_0-1}^2 > 0 . This gives ( a n 0 + a n 0 1 ) ( a n 0 a n 0 1 ) > 0 (a_{n_0} + a_{n_0-1})(a_{n_0} - a_{n_0-1}) > 0 , and since a n 0 + a n 0 1 > 0 a_{n_0} + a_{n_0-1} > 0 , we can divide both sides by a n 0 + a n 0 1 a_{n_0} + a_{n_0-1} without changing the direction of the inequality, giving a n 0 a n 0 1 > 0 a_{n_0} - a_{n_0-1} > 0 or a n 0 > a n 0 1 a_{n_0} > a_{n_0-1} . This proves the inductive claim.

Since { a n } \{a_n\} is a sequence of real numbers that is increasing and bounded, it has a limit L L . This limit satisfies L = 18 + 3 L L = \sqrt{18 + 3L} , or,

L 2 = 18 + 3 L L 2 3 L 18 = 0 ( L + 3 ) ( L 6 ) = 0 \begin{aligned} L^2 &= 18+3L \\ L^2 - 3L - 18 &= 0 \\ (L+3)(L-6) &= 0 \end{aligned}

This gives L = 3 L = -3 or L = 6 L = 6 . Since { a n } \{a_n\} is increasing and a 1 > 0 > 3 a_1 > 0 > -3 , clearly the limit cannot be 3 -3 , and thus the limit is 6 \boxed{6} .

Moderator note:

A thorough analysis. Great!

you need to said by completeness theorem the limit exist

Ramez Hindi - 6 years, 1 month ago

Log in to reply

Good point; added above, with a n a_n being a sequence of real numbers. (Real numbers is complete so we can invoke the monotone convergence theorem.)

Ivan Koswara - 6 years, 1 month ago
Otto Bretscher
May 8, 2015

Let's keep this as simple as we can while still being rigorous.

Consider the continuous function f ( x ) = 18 + 3 x f(x)=\sqrt{18+3x} defined on [ 0 , 6 ] [0,6] .

We start with a few straightforward observations: (a) f ( x ) f(x) is increasing, (b) f ( 6 ) = 6 , f(6)=6, (c) f ( x ) > x f(x)>x for x < 6 x<6 , (d) The range of f ( x ) f(x) is [ 18 , 6 ] [\sqrt{18},6] , by properties (a) and (b), so that we can iterate f ( x ) f(x) since the range is a subset of the domain.

Now consider the sequence recursively defined by a 1 = 18 a_1=\sqrt{18} and a n + 1 = f ( a n ) a_{n+1}=f(a_n) . By properties (c) and (d), this sequence is increasing and bounded by 6, so that it has a limit L 6 L\leq6 by completeness. By continuity of f ( x ) f(x) , we have f ( L ) f(L) = lim n f ( a n ) =\lim_{n\to\infty}f(a_n) = lim n a n + 1 = L =\lim_{n\to\infty}a_{n+1}=L , so that L = 6 L=\boxed{6} by properties (b) and (c).

Vishal Gupta
May 6, 2015

you need to prove the existence of limit by using completeness theorem

Ramez Hindi - 6 years, 1 month ago

Log in to reply

how do we do that? i don't know what completness theorem is

Akash Gaonkar
May 10, 2015

We can say that the solution is the last term of the series a n = 18 + 3 a n 1 ; a 0 = 1. a_n = \sqrt{18+3a_{n-1}}; a_0 = 1.

We proceed by hoping this series converges, and writing a program that iteratively calculates the next value in the series.

import math

a = 1
for i in range(20):
    a = math.sqrt(18 + a * 3)
    print(a)

The values of a a converge to 6 at the degree of accuracy of a float.

Chinmay Kurdekar
May 2, 2015

Let y = ( 18 + 3 ( 18 + 3 ( 18 + 3 18 + . . . . . . y=√(18+3√(18+3√(18+3√18+...... Square RHS and LHS

y 2 = 18 + 3 y y^2=18+3y

After solving the above quadratic equation, We get y = 6 y=6

Moderator note:

For clarity, you should explain why y 3 y\ne -3 .

LET, the given problem be taken as a function on x where 18+3sqrt(18+.....))))..... be taken as x. now, f(x)= sqrt(18+3sqrt(18+3sqrt)18+....))))))... = sqrt(x) so by property of function any x under sqrt is > or = 0. so x is positive. solving the equation in the form of quadratics we get, x=6 or x=-3. but x is +ve. so x=6

Let x be the required number. Then we note that (x^2)=18+3x, which is the quadratic equation (x^2)-3x-18=0. Factoring the right-hand side of the equation, we obtain (x+3)(x-6)=0 so that x=-3 or x=6. But x cannot take negative values. So x=6 is the only solution. Therefore, the answer is 6.

Ramesh Sridharan
May 9, 2015

I'm curious why answer can't be negative. Square root of something came me plus or minus, right?

By definition a radical sign means the positive square root.

Linda Muratore - 6 years, 1 month ago
Pradeep Pradhan
May 8, 2015

just guessed

Jeremy Ang
May 2, 2015

Let x be the expression, therefore

x=√(18+3√(18+3√(18+......

x=√(18+3x)

x² =18+3x

x²-3x-18=0

(x+3)(x-6)=0

x=-3;x=6

Ignoring complex answers(√negative number)

Therefore, x=6

Moderator note:

For clarity, you should explain why x 3 x\ne -3 .

if we consider that the problem statement defines continuous additive growth which converges to value x=6 & then we take x=-3 as the answer this means we expect continuous reduction & finally converging to x=-3, that violate our assumption in first statement. Thus correct answer is 6.

Umesh Masurekar - 6 years, 1 month ago

Bcoz √ x^2x^2=|x| i.e. always +ve

Aditya Chauhan - 6 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...